Characterizing Sociostructural Associations With New HIV Diagnoses Among Female Sex Workers in Cameroon. (1st March 2019) - Bowring, Anna L.; Ketende, Sosthenes; Billong, Serge C.; Mfochive Njindam, Iliassou; Rao, Amrita; Decker, Michele R.; Lyons, Carrie; Turpin, Gnilane; Fako, Guy; Olawore, Oluwasolape; Ndonko, Flavien; Levitt, Daniel; et al.
Abstract : Background: Female sex workers (FSW) are disproportionately affected by HIV in Cameroon, with an estimated 23.6% HIV prevalence. Given the unavailability of HIV incidence data, to better understand associations with acquiring HIV we assessed the prevalence and associations with new HIV diagnoses among FSW in Cameroon. Methods: In 2016, FSW were recruited through respondent-driven sampling from 5 cities for a biobehavioral survey. Participants self-reporting living with HIV or with an indeterminate test status were excluded from analysis. New diagnoses were defined as testing HIV-positive when participants self-reported HIV-negative or unknown status. A multivariable modified Poisson regression model was developed to assess determinants of new HIV diagnosis (referent group: HIV-negative) using key covariates; adjusted prevalence ratios (aPR) are reported if statistically significant ( P < 0.05). Results: Overall 2255 FSW were recruited. Excluding participants who self-reported living with HIV (n = 297) and indeterminate test results (n = 7), 260/1951 (13.3%) FSW were newly diagnosed with HIV. Variables significantly associated with new HIV diagnosis were: no secondary/higher education [aPR: 1.56, 95% confidence interval (CI): 1.12 to 2.15], 5+ dependents compared with none (aPR: 2.11, 95% CI: 1.01 to 4.40), 5+ years involved in sex work compared with <1 year (aPR: 2.84, 95% CI: 1.26 to 6.42), history of incarceration (aPR: 2.13, 95% CI: 1.13 to 3.99), and low social capital (aPR: 1.53, 95% CI: 1.12 to 2.10). Higher monthly income (>250, 000 FCFA vs. <50, 000 FCFA) was associated with lower prevalence of new HIV diagnosis (aPR: 0.22, 95% CI: 0.05 to 0.86). Conclusions: There are significant sociostructural factors that seem to potentiate risk of HIV infection and delay diagnosis among FSW in Cameroon. Initiatives to build social capital and integrate services such as pre-exposure prophylaxis and HIV self-testing into HIV programs may reduce new infections and decrease time to diagnosis and treatment. Abstract : Supplemental Digital Content is Available in the Text.